2015
DOI: 10.5372/1905-7415.0905.431
|View full text |Cite
|
Sign up to set email alerts
|

CT features of normal lung change in asymptomatic elderly patients

Abstract: Background: Not all morphological lung changes in the elderly contribute to respiratory disease and may be a consequence of normal aging. Objectives: To describe the changes in asymptomatic elderly patients compared with those in younger patients in a Thai population. Methods: The study cohort comprised 60 participants without respiratory symptoms in three groups of 20 by age: 20−40 years, 41−60 years, and >60 years. Participants were prospectively selected from patients referred for computed tomography (CT) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In this study, examination of the CT images included quantitative measurements and search for multiple possible lesions based on previous studies of CT signs in aged humans; however, few examples were found of ground glass pattern, bronchial thickening, or bronchial dilation, and no signs of reticular pattern, emphysema, pleural thickening, or septal thickening were identified in any dog. Hence, finding any of these features in CT images of a dog with respiratory signs suggests the presence of nonage‐related lung pathology that is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, examination of the CT images included quantitative measurements and search for multiple possible lesions based on previous studies of CT signs in aged humans; however, few examples were found of ground glass pattern, bronchial thickening, or bronchial dilation, and no signs of reticular pattern, emphysema, pleural thickening, or septal thickening were identified in any dog. Hence, finding any of these features in CT images of a dog with respiratory signs suggests the presence of nonage‐related lung pathology that is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The number of dogs available for study was limited by the need to avoid including dogs likely to have had pathologic lung lesions. Use of a single observer to review the CT is also a limitation, but this is not considered to be a major problem because of the relatively homogenous nature of the study sample and use of comprehensive, preconsidered assessment criteria based on previous studies of humans …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In symptomatic patients, thickening of the walls of the small airways is associated with various reactive and inflammatory conditions [11,12]. On the other hand, such finding is commonly seen in elderly asymptomatic cases, typically win the thickening is of mild or moderate degree [1,3]. Mosaic attenuation due to air trapping has a known association with small airway disease, including bronchial wall thickening [4,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several ageing-related morphological lung changes can be detected by computed tomography (CT), many of which are incidentally seen in asymptomatic populations [1][2][3][4][5]. Such findings include bronchial wall thickening, bronchial dilatation, mosaic attenuation from air trapping, pneumatocoeles, linear opacities and reticulations [1,2,4,6,7].…”
Section: Introductionmentioning
confidence: 99%